Happy first birthday SWJPCC! - Robbins RA (Southwest Journal of Pulmonary and Critical Care, 2012)
No abstract available. Article truncated at 150 words. With the end of 2011, the Southwest Journal of Pulmonary and Critical Care (SWJPCC) completed its first full year of operation. Planning for SWJPCC began in August, 2010 and our first manuscript was posted on November 11, 2010. This has been a year of growth. We posted 8 manuscripts our first year and 68 this year (Table 1). Table 1. Postings by SWJPCC 2010 and 2011. We had manuscripts submitted from each fellowship programs in the Southwest (Phoenix, Tucson, Albuquerque and Denver) but also received submissions from outside the Southwest including from foreign countries such as the UK, India and Boston (which views itself as a separate country). Our readership has also steadily grown from 30 unique IP addresses in November, 2010 to nearly 1000 during December, 2011 (Figure 1, Panel A). Accompanying this increase in uniques has been an increase in the number of page views (the number of …